Susceptibility to Yersinia pseudotuberculosis Infection is Linked to the Pattern of Macrophage Activation - Tansini, A. [UNESP]; de Medeiros, B. M. M. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
T helper 1 cells play a crucial role in the clearance of Yersinia pseudotuberculosis infection. By producing cytokines and presenting antigens to T cells, activated macrophages can orientate the adaptive immune response. The pathway used by macrophages to metabolize arginine has been employed as an important parameter to discriminate their activation state. In this study, the pattern of macrophage activation in Y. pseudotuberculosis-infected BALB/c (Yersinia-susceptible) and C57BL/6 (Yersinia-resistant) mice and their immunostimulatory capacity were analysed. In the early phase of infection, macrophages obtained from C57BL/6 mice produced higher levels of NO, lower arginase activity, and larger amounts of IL-12 and TNF-alpha than macrophages from BALB/c mice. on the other hand, macrophages derived from BALB/c mice produced higher levels of IL-10 and TGF-beta than C57BL/6 mice. The Y. pseudotuberculosis infection leads to a fall in the macrophage immunostimulatory capacity of both strains of mice, with T-cell proliferation significantly reduced 12 h after infection. Moreover, we observed in the supernatant of co-culture of macrophages from infected mice with T lymphocytes from heat-killed Yersinia-immunized mice lower IFN-gamma production by cells from BALB/c mice than by C57BL/6 mice, and IL-4 was produced only by BALB/c mice on the first- and third-day post-infection. These results suggest that the pattern of macrophage activation is associated with susceptibility and resistance to Y. pseudotuberculosis infection in BALB/c and C57BL/6 mice.